2014
DOI: 10.3109/02699052.2014.887145
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit hyperactivity disorder as a risk factor for concussions in NCAA division-I athletes

Abstract: ADHD is prevalent in NCAA Division-I athletes and associated with history of past concussions. If replicated, these findings could have important implications in the prevention and management of concussions in athletes with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 17 publications
2
76
0
1
Order By: Relevance
“…53 In addition, previous retrospective work has demonstrated that children with ADHD and collegiate athletes with ADHD are more likely to self-report a history of concussion. 54,55 However, the fact that the effect sizes were generally equivalent for analyses with and without athletes with self-reported ADHD suggests that the observed differences in cortical thickness were not principally driven by ADHD. However, the interaction between ADHD, cortical thickness, and concussion history requires future investigation in larger sample sizes.…”
Section: Discussionmentioning
confidence: 97%
“…53 In addition, previous retrospective work has demonstrated that children with ADHD and collegiate athletes with ADHD are more likely to self-report a history of concussion. 54,55 However, the fact that the effect sizes were generally equivalent for analyses with and without athletes with self-reported ADHD suggests that the observed differences in cortical thickness were not principally driven by ADHD. However, the interaction between ADHD, cortical thickness, and concussion history requires future investigation in larger sample sizes.…”
Section: Discussionmentioning
confidence: 97%
“…However, other research has addressed these issues (e.g., Gerber, Ginsberg, & Reift, 1992; Stack-Cutler, Parrila, Jokisaari, & Nurmi, 2013), which merit further research. Future research should also focus on other handicapping conditions affecting reading and writing in adolescents and young adults such as attention deficit disorder (Zuckerman, Lee, Odom, Solomon & Sills, 2013), mild head injuries (Beers, Goldstein, & Katz, 1994), and concussions (Alosco, Fedor, & Gunstad, 2014; Collins et al, 1999; Griffin, 2015; Covassin, Elbin, McAllister, & Whalen, 2014; Hunt, McCamey, & Beisner, 2010; Solomon & Haase, 2008). Future research should also address linking assessment to instruction for a variety of conditions affecting learning in adolescents and young adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, only one study in this review excluded subjects with prior history of headache . In addition, attention deficit‐hyperactivity disorder (ADHD) may also lead to worsened outcomes . In prior research, ADHD was associated with about a 3 times prevalence of having had 3 or more concussions and learning disorder was associated with about a 2 times prevalence of having had 3 or more concussions.…”
Section: Discussionmentioning
confidence: 99%